Strategi Marketing Public Relations Toko Fashion: (Studi Deskriptif Analisis pada ISOOS STUDIOS) - Naurah Syifa; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2023)
Abstract. Marketing public relations is an activity of identifying, creating, and communicating value and establishing relationships with customers to maximize company profits. Three Ways Strategy is a marketing public relations strategy that can be used as a way to stimulate consumers to purchase products. This research was conducted to determine the push, pull, and pass strategy factors used by ISOOS STUDIOS Stores. This study uses a positivism paradigm, a quantitative method with a qualitative data descriptive study approach or analysis descriptive study. The data collection technique used was by interviewing and observing the informant owner and marketing manager of ISOOS STUDIOS. The data analysis technique in this study was by member checking. The results of this study are: (1) Push Strategy through the consignment store system which then has an expo through exclusive releases and publishes to the consignment store through proposals and direct reports via groups or Google sheets as well as routine product launching activities; (2) The Pull Strategy is carried out by publishing products online on social media, e-commerce, and the web. Also witnessed offline through fashion shows, pop up stores, annual exhibitions, and exhibition launches. As well as making broadcast messages, campaigns, giveaways, and also QR customer satisfaction surveys; (3) Pass Strategy through collaborative communication with the media, disaster awareness activities, donations to people and places in need, sponsorship and collaboration events. Keywords: Marketing Public Relations, Pass Strategy, Pull Strategy, Push Strategy. Abstrak. Marketing public relations merupakan suatu kegiatan mengidentifikasi, menciptakan, dan mengomunikasikan nilai serta menjalin hubungan-hubungan dengan pelanggan untuk memaksimalkan laba perusahaan. Three Ways Strategy merupakan salah satu konsep strategi marketing public relations yang dapat dijadikan salah satu cara untuk merangsang konsumen terhadap pembelian produk. Penelitian ini dilakukan untuk mengetahui faktor push, pull, dan pass strategy yang digunakan oleh Toko ISOOS STUDIOS. Penelitian ini menggunakan paradigma positivisme, metode kuantiatif dengan pendekatan studi deskriptif data kualitatif atau studi deskriptif analisis. Teknik pengumpulan data yang digunakan yaitu dengan wawancara dan observasi terhadap informan owner dan marketing manager ISOOS STUDIOS. Teknik analisis data dalam penelitian ini dengan membercheck. Hasil penelitian ini adalah : (1) Push Strategy melalui system consignment store yang kemudian terdapat expo melalui exclusive release dan mempublikasikan kepada consignment store melalui proposal dan report direct via group atau google sheet juga kegiatan launching product rutin; (2) Pull Strategy dilakukan publikasi produk secara online di media sosial, e-commerce, dan web. Juga disaksikan offline melalui fashion show, pop up store, pemeran tahunan, dan exhibition launch. Serta membuat broadcast message, campaign, giveaway, dan juga QR survei kepuasan pelanggan; (3) Pass Strategy melalui komunikasi kerjasama dengan media, aktivitas kepedulian bencana, sumbangan ke orang juga tempat yang membutuhkan, sponsorship serta collaboration event. Kata Kunci: Marketing Public Relations, Pass Strategy, Pull Strategy, Push Strategy.